The Influence of Green Entrepreneurial Behavior on The Availability of Wood Raw Materials in Wood Processing Msmes in Ngawi Regency - Yuwono Kartiko; Istiana Wijayanti Mala (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the influence of green entrepreneurial behavior on the availability of wood raw materials among wood-processing MSMEs in Ngawi Regency. The study employed a qualitative approach using a descriptive research design. Data were collected through in-depth interviews, observations, and documentation. The research informants consisted of wood-processing MSME owners, wood raw material suppliers, and relevant institutions. Data analysis was conducted using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The findings indicate that several MSMEs have implemented green entrepreneurial behavior through efficient use of raw materials, utilization of wood waste, use of legally sourced wood, and reduction of production waste. The implementation of such practices helps maintain the continuity of wood raw material availability while supporting business sustainability. However, the implementation of green entrepreneurship still faces several challenges, including limited capital, low understanding of environmentally friendly business practices, and inadequate technological support and training. This study concludes that green entrepreneurial behavior plays an important role in maintaining the availability of wood raw materials and ensuring the sustainability of wood-processing MSMEs in Ngawi Regency.